Dual variants of uncertain significance in a case of hyper-IgM syndrome: implications for diagnosis and management - Agrebi, Nourhen; Mackeh, Rafah; Alsabbagh, Mohamed; Elmi, Asha; Al-Marri, Amnah A.; Hubrack, Satanay Z.; Purayil, Saleema C.; Karim, Mohammed Yousuf; Hassan, Amel; Lo, Bernice (Frontiers in Immunology, 2025)
BackgroundHyper-IgM syndrome (HIGM) is a genetic immunodeficiency characterized by elevated to normal IgM levels and decreased IgG, IgA, and IgE. The overlapping clinical presentations of different gene mutations complicate diagnosis and management.ObjectiveThis study aims to elucidate the clinical implications of concurrent AICDA and IKBKB homozygous variants in a pediatric patient diagnosed with hyper-IgM syndrome.MethodsWe present immunological and genetic analysis of a Tunisian patient with two homozygous variants of uncertain significance (VUSs) in the IKBKB and AICDA genes, suspected of causing hyper-IgM and immune deficiency. We conducted functional tests to ascertain the pathogenicity of IKBKB and AICDA mutations and to provide a definitive diagnosis and appropriate management.ResultsGenetic analysis identified two homozygous variants: AICDA (p.W80S) and IKBKB (p.R77Q). Immunophenotyping and functional studies found greatly reduced class-switched memory B cells and somatic hypermutations but normal T cell responses and NFkB activation.ConclusionThe simultaneous presence of multiple homozygous VUSs emphasizes a major challenge in the genetic diagnosis of highly consanguinous patients. Functional workup as well as familial segregation studies are needed to clarify variant pathogenicity and provide a definitive diagnosis and tailored treatment strategies for these patients. Our studies suggest that the AICDA p.W80S variant is pathogenic, while the IKBKB p.R77Q variant is likely benign.